Pengaruh Media Pocketbook terhadap Ketrampilan/Skill Pertolongan Pertama dengan Metode R-I-C-E pada Korban Ankle Sprain - Widyarani, Linda; Kustanti, Cecilya (Universitas Malahayati, 2024)
ABSTRACT Ankle sprain is a soft tissue musculoskeletal injury that occurs suddenly. The R-I-C-E approach, which stands for Rice, Ice, Compression, and Elevation, is recommended as first aid for ankle sprains. The general public's understanding of first aid for ankle sprains is still limited. Health education delivered through pocketbook media can help to increase public awareness. The purpose of this study was to determine the effect of pocketbook media on first aid skills using the R-I-C-E technique in ankle sprain patients. This study was a quantitative study with pre experimental design with one group pre-post test design. The statistical test that used was paired-t test. The population in this study were health cadres in Desa Karangtalun, Imogiri, Bantul, Daerah Istimewa Yogyakarta with a total sample of 30 people. Times of researcher on February until March 2023. In this study, the mean pre-test score was 54,80±2,265 and the mean post-test score was 73,73±1,999, with the results of paired-t test statistic being p = 0.000 (< 0.05), meaning that there is a significant difference in skills score between before and after being given the pocketbook media in the discharge planning pro on first aid skills using the R-I-C-E technique in ankle sprain patients. The pocketbook media has a beneficial impact on health cadres’s skills of how to provide first aid skills using the R-I-C-E technique in ankle sprain patients. In order to provide first aid skills using the R-I-C-E technique in ankle sprain patients, health cadres Desa Karangtalun, Imogiri, Bantul, Daerah Istimewa Yogyakarta, can use the pocketbook media as a guide or reference. Keywords: Pocketbook, Ankle Sprain, First Aid ABSTRAK Ankle sprain adalah cedera pada jaringan lunak yang terjadi secara tiba-tiba. Metode R-I-C-E, yaitu Rice, Ice, Compression dan Elevation merupakan pertolongan pertama pada ankle sprain. Pengetahuan dan pemahaman masyarakat tentang pertolongan pertama pada ankle sprain masih rendah. Pendidikan kesehatan melalui media pocketbook dapat membantu meningkatkan pemahaman masyarakat tentang pertolongan pertama pada ankle sprain. Penelitian ini bertujuan menganalisis pengaruh media pocketbook terhadap peningkatan ketrampilan/skill kader kesehatan dalam memberikan pertolongan pertama pada korban dengan ankle sprain. Penelitian ini adalah studi kuantitatif, pre experimental design dengan one group pre-post test design. Analisis data menggunakan uji paired t-test. Responden pada penelitian ini adalah kader kesehatan yang bertempat tinggal di Desa Karangtalun, Kecamatan Imogiri, Kabupaten Bantul, Provinsi Daerah Istimewa Yogyakarta, berjumlah 30 orang. Penelitian ini dilakukan pada Bulan Februari hingga Bulan Maret 2023. Penelitian ini menunjukkan bahwa rerata ketrampilan/skill responden sebelum intervensi adalah 54,80 ± 2,2, sedangkan rerata ketrampilan/skill responden sesudah intervensi adalah 73,73 ± 1,99 dengan p = 0,000. Uji statistik tersebut menunjukkan terdapat perbedaan ketrampilan/skill responden sebelum dan sesudah pemberian pendidikan kesehatan melalui media pocketbook. Media pocketbook memberikan dampak positif bagi kader kesehatan yang bertempat tinggal di Desa Karangtalun, Kecamatan Imogiri, Kabupaten Bantul, Provinsi Daerah Istimewa Yogyakarta. Kader kesehatan dapat lebih mudah memahami cara/teknik/prosedur pemberian metode R-I-C-E pada korban dengan ankle sprain melalui media pocketbook ini. Kata Kunci: Pocketbook, Ankle Sprain, Pertolongan Pertama